A study on the simulation method for fatigue damage behavior of reinforced concrete structures. (1st November 2017) - Liang, Junsong; Nie, Xin; Masud, Mahadi; Li, Jie; Mo, Y.L.
Highlights: The manuscript has been revised carefully according to the comments and advices of the reviewers. An efficient method for the simulation on fatigue behavior of reinforced concrete structures is proposed. Fatigue damage accumulation for both concrete and reinforcement are considered and modeled. An expediting calculation technique for fatigue simulation is developed. High efficiency fatigue simulations on reinforced concrete structure are performed. Abstract: This paper mainly focuses on developing an efficient simulation method for fatigue behavior of reinforced concrete structures (RC structures), through which the damage state and the potential fatigue damage failure pattern of the RC structures could be obtained in finite element analysis (FEA). In order to accomplish such object, fatigue behavior of RC structures is studied using the entire history of damage accumulation for both concrete and steel bars. A bi-scalar damage-plasticity constitutive model for concrete and a single-scalar damage constitutive model for reinforcement are first introduced to characterize the fatigue damage state of the structure. Then, a two-scale temporal expediting computational technique is developed for the material constitutive models, by which the original material models could be split into a micro periodic time scale portion and a macro homogenized time scale portion. Through this calculation technique, the original increment-by-increment FEA procedures could be transferred to the two-time scale calculation, which would greatly enhance the efficiency of the structural fatigue simulation. By combining the material constitutive models and the expediting calculation technique with FEA, a set of numerical examples and comparisons are performed, specifically, a column-drilled shaft connection in bridge structure is simulated, which validates the effectiveness and reliability of the current simulation method for the fatigue behavior of RC structures.